Development of the Professional Competence of the Future Specialist Using Internet Technologies - Adamia, Zoia K.; Biletskyi, V. S.; Onkovich, Hanna V.; Onkovich, Аrtem D. (Publisher agency, 2023)
The article examines and analyzes the peculiarities of Internet didactics and its components in order to increase the effectiveness of the educational process and scientific research. Examples illustrate the use of blog didactics, Wikididactics, webinar didactics, and specialized online lecture courses. In the context of Internet didactics, the topic of information reliability is raised. As an example, the modern Ukrainian classification of scientific and educational publications is presented. Formulated methodical approaches and recommendations for their use.
Keywords: media culture; media didactics; media didactics of higher school; nternet didactics; media education; professionally oriented media education; professional competence; media competence; professionally oriented special course; development of professional competence